Impact of text-based flipped instruction on grade 12 students’ academic achievement in acid–base concepts - Ametepey, Israel; Mpuangnan, Kofi N; Ankudze, Bright (Edelweiss Applied Science and Technology, 2026)
This study assessed academic achievement of Grade 12 students in acid-base concepts at Ada Senior High Technical School in Ghana. The study was framed by Social Constructivism theory proposed by Lev Vygotsky. To achieve the aim, quantitative method was used together with a quasi-experimental, pre-test/post-test design. A sample of 21 third-year Agricultural Science students were selected through the cluster sampling technique. A Likert-scale questionnaire was used to collect the data. Descriptive and inferential statistics were employed to analyze the data collected. The results show that students’ posttest scores (M = 15.81, SD = 2.32) compared to pretest scores (M = 10.33, SD = 3.97), t (20) = –6.87, p < 0.001 were significance improvement in the teaching approach with a large effect size (Cohen’s d = 3.66). Additionally, the results on the academic achievement of the students (M = 4.59, p < 0.001) show the flipped learning model has a positive effect on the students’ learning outcomes. This affirms that flipped learning approach improved their conceptual understanding, promoted engagement, and increased learning responsibility. It was recommended the Ghana Education Service should employ flipped learning approach into chemistry curriculum frameworks to improve teaching and learning of abstract topics like acid-base concepts.